2020
DOI: 10.1101/2020.02.28.969758
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cold Atmospheric Plasma induces silver nanoparticle uptake, oxidative dissolution and enhanced cytotoxicity in Glioblastoma multiforme cells

Abstract: Running title: Cold Atmospheric Plasma enhances silver nanoparticle uptake and cytotoxicity.2 Abstract Silver nanoparticles (AgNP) emerged as a promising reagent for cancer therapy with oxidative stress implicated in the toxicity. Meanwhile, studies reported cold atmospheric plasma (CAP) generation of reactive oxygen and nitrogen species has selectivity towards cancer cells. Gold nanoparticles display synergistic cytotoxicity when combined with CAP against cancer cells but there is a paucity of information usi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 78 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…Recently, it has been demonstrated that CAP treatment has synergistic anti-cancer effects in combination with various nanoparticles, including gold nanoparticles 12 , silver nanoparticles 13 , iron nanoparticles 14 and iron oxide-based magnetic nanoparticles 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been demonstrated that CAP treatment has synergistic anti-cancer effects in combination with various nanoparticles, including gold nanoparticles 12 , silver nanoparticles 13 , iron nanoparticles 14 and iron oxide-based magnetic nanoparticles 15 .…”
Section: Introductionmentioning
confidence: 99%